Estimating cetacean population trends from static acoustic monitoring data using Paired Year Ratio Assessment (PYRA). - Eric P M Grist; Trevelyan J McKinley; Saptarshi Das; Tom Tregenza; Aileen Jeffries; Nicholas Tregenza (PLoS ONE, 2022)
The cetacean conservationist is often faced with evaluating population trends from abundance data that are either sparse or recorded at different times in different years. The presence of diel or seasonal patterns in the data together with unplanned gaps is often problematic. Such data are typical of those obtained from static acoustic monitoring. We present a simple and transparent non-parametric trend evaluation method, 'Paired Year Ratio Assessment (PYRA)' that uses only whole days of data wherever they are present in each of successive pairs of periods of 365 days. We provide a quantitative comparison of the performance of PYRA with traditional generalised additive models (GAMS) and nonparametric randomisation tests that require a greater level of skill and experience for both application and interpretation. We conclude that PYRA is a powerful tool, particularly in the context of identifying population trends which is often the main aim of conservation-targeted acoustic monitoring.